Structural irregularity quantification in buildings using vital signs. (December 2021) - Archana, A.R.; Akbar, M. Abdul
Abstract: The complexity of structural irregularity guidelines in seismic design codes is increasing with revised versions of the code to cater to increased construction of iconic shaped buildings coupled with lessons learnt from building failures during past earthquakes. This short communication paper intends to present a medical approach to check the irregularity of a building based on common parameters which are indicators of its deviance from a regular configuration. Similar to the "vital signs" in medical profession, namely, body temperature, pulse rate, respiratory rate and blood pressure which are indicators of health of a human body or its disease-free state, the extend of irregularity of building structures is quantified by four parameters considered as "vital signs" in buildings, namely, time period, average support reaction per bay, distance between center of mass and center of rigidity and lateral displacement of diaphragm center of mass with increasing storeys. An implementation of the approach is demonstrated based on the analysis and result interpretation carried out on five storied building models. The outcomes of regular and irregular buildings differed significantly, which shows that there exists a similar relationship between the seismic response of buildings with various types of irregularities and can be represented using common parameters that need to be incorporated in future revisions of sesmic design codes.